Strategi Branding dan Digital Marketing Kripik Antari Olahan Tepung Singkong (Mocaf) untuk Mendorong Pertumbuhan Omzet dan Daya Saing UMKM Desa Kemasantani - Edwin Pondi Suwanto; Kafi Udin; Julia C; Vela Prawesti; Devia Ariana P; Dicky Arganata W; Ikhwanul Muslimin; Dimas Erlanga; Firdaus Firman F; Gesang Ardi Ramadhan; Robby Mukhammad K; Muhammad Rizky Yoga P; Ignatius Garvindo Firstelda P; Merdinda Afifa Dewi Dian Try Damayanti1; Fanny Athala Priherliansyah; Heven Ramadani; Satria Dava Hari Wijaya; Roma dhoni Aulia Billah; Putri Sari; Alivia Halimatus Sha’diyah; Cantika Lintang Maharani S P; Rima Aulia Firdaus; Aliffian Bagus P; Meri Andani (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Kemasantani Village have considerable potential in developing cassava-based products using MOCAF flour, particularly Antari chips. However, limited brand identity, unattractive packaging, and the underutilization of digital marketing have constrained product competitiveness and revenue growth. This community service program aimed to strengthen branding and optimize digital marketing strategies to support MSME revenue growth. A qualitative participatory approach was employed through surveys, interviews, observations, documentation, and direct assistance in brand identity development, packaging redesign, and social media management. The results indicate improvements in product image, packaging attractiveness, and market reach through digital platforms. The integrated application of branding and digital marketing successfully increased consumer engagement and led to an approximate 35% increase in MSME revenue within a three-month period. These findings suggest that strategic branding and digital marketing are effective approaches for enhancing competitiveness and ensuring the sustainability of locally based MSMEs in rural areas.